Predictors of Central Obesity in Perimenopausal Women: An Analysis of Food Craving, Diet Quality, and Physical Activity - Mahardika Yudianti, Manda Talitha; Kusnandar, Kusnandar; Widyaningsih, Vitri (Journal of Health and Nutrition Research, 2025)
Central obesity, an accumulation of abdominal fat, which can be measured using waist circumference, is a health risk that may increase during the perimenopausal transition. Central obesity is caused by various factors, which include, environmental and behavioral factors (physical activity and eating behavior). Eating behaviors that contribute to obesity include a strong desire to consume certain types of food/food craving. Poor eating habits such as consuming high-calorie foods, fast food consumption, and not consuming a variety of foods will affect one's diet quality. This cross-sectional study with multistage sampling method collected data from 125 women with perimenopausal symptoms. Data were collected via interviewer-administered validated questionnaires. Statistical analysis was conducted using SPSS software 25. The results indicated that 63.2% of the respondents had central obesity, 40,5% of those sometimes experienced food cravings. Most respondents with central obesity (94,9%) and non-central obesity (84,8%) had a very poor diet quality, and 40,5% of respondents with central obesity had vigorous activity, compared to 47.8% among women without central obesity. There was significant correlation between food craving (OR = 1.091; 95% CI = 1,04 – 1,14), diet quality (OR = 0.916; 95% CI = 0,86 – 0,96) with central obesity (p<0,05). There was no significant correlation between physical activity, education level, and socioeconomic status with central obesity (p>0,05). In conclusion, diet quality and food craving significantly influence the incidence of central obesity in women with perimenopausal symptoms in Bukittinggi City.